Evaluation of Edible Quality of Sorghum Based on Principal Component Analysis - Chunlei Ni; Shan Zhang; Gaopeng Zhang; Jianjun Cheng; Huanyu Zheng (Journal of Chemistry)
Sorghum (Sorghum bicolor (L.) Moench) is one of the most important cereals in the Northeast China. The physicochemical, pasting, texture, and cooking properties of 21 sorghum varieties were determined, which were mainly cultivated in Northeast China. Then, the evaluation of edible quality of sorghum was based on principal component analysis and fitted with the score of sensory evaluation. Five principal components (PCs) with a cumulative contribution rate of 86.19% could be picked out to describe the taste, pasting, flavor, cooking, and variety of sorghum, respectively. And a comprehensive equation of sorghum edible quality in Northeast China was constructed which was Z = 0.45F1 + 0.25F2 + 0.12F3 + 0.10F4 + 0.08F5. The edible quality of No. 14 and No. 15 was the best. The sensory evaluation was used to verify the above equation with the fitting coefficient of 0.81, which indicated that the equation could be more accurate to evaluate the edible quality of sorghum in Northeast China.